TINJAUAN TENTANG KESESUAIAN ISI BUKU TEKS BAHASA JEPANG KELAS X SMA BINAAN KHUSUS DUMAI DENGAN KURIKULUM 2013 - Rahayu, Nana Rahayu; Aibonotika, Arza Aibonotika; ', Ruziqna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the suitability of the contents of Japanese textbooks grade X SMAN Binaan Khusus Dumai by curriculum 2013. This study curriculum are conducted in Japanese Language Study Program FKIP, University of Riau. Retrieval time and research that in March 2015 to May 2015. The object of research is the Japanese textbook curriculum that is labeled 2013. On the accuracy of the material has 8 points which are the points covered in the textbook, but there are also points that are not covered in textbook. Based on feasibility analysis of the contents of the textbook Japanese な か よ く に ほ ん で (Naka yoku Nihon de) published Rizqi Press in 2011 on the suitability of a description of material with this competence, basic competence contained grains of conformity in accordance with the curriculum in 2013, and grains that are not found in textbooks with curriculum in 2013, whereas the accuracy of the suitability of the material contained grains that have suitability in accordance with the curriculum in 2013, and grains that are not found in textbooks with curriculum 2013 Keywords: Curriculum 2013, textbook